Empowerment of Women in The Informal Sector to Increase Household Income : Case Study in Sleman - Susianti, Susianti (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
This study aims to identify and analyze women’s empowerment in the informal sector. The involvement of women in earning a living shows the role of women increasingly evident in economic allocation. This is an opportunity for women to carry out production activities in the midst of economic conditions that are less supportive for subsistence economic groups. Various types of informal economic activities are carried out by women while considering the allocation of time for families and routine household work. One of the informal economic activities that many women do is a household stall business. Problems that are still found in the household stall business are related to its market share which has limited demand. In this case, turnover of stalls also depends on the increase in consumption or the amount that can be spent by the surrounding community. Without an increase in the income of the business community, it is difficult to expect an increase in purchasing power and consumption levels even though this household stall is one source of women’s income to help sustain household life. This research is quantitative with a purposive sampling method for sampling. The research was conducted in Sleman, DI Yogyakarta. From the multiple linear regression analysis with the OLS method used shows that from the variables of capital, education, age and working hours of women working in the informal sector in Sleman, the variables of work capital and education have positive and significant coefficients. Meanwhile, the results of descriptive analysis show that the main reasons and motivations that encourage women to work in the informal sector in Sleman, DI. Yogyakarta are to increase household income to meet their needs.